(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Sharanda V. Ye. Forming primary school teachers’ linguistic competence at higher schools of the first and second level of accreditation in the process of professional training. The article is devoted to the pedagogical fundamentals of forming primary school teachers’ linguistic competence at higher schools of the first and second level of accreditation in the process of professional training. The author analyzes the concept of linguistic competence, the theoretical fundamentals of its formation, and the levels of its development. The author also presents the technique of forming primary school teachers’ linguistic competence in the process of professional training.